Faktor-Faktor Yang Mempengaruhi Terhadap Kunjungan Wisatawan Lokal Di Kebun Stroberi (Fragariachoiloensis L.) Kawasan Wisata Tongkoh Kabupaten Karo - Listra Berutu; Bambang Hermanto; Gustami Harahap (Mahesa Research Institute, 2023)
This Self Picking Strawberry Garden is one of the tourist locations for Strawberry plantations that offers a different feel from tourist attractions in general, namely buying strawberries by picking directly from the tree, and offering the cool air and the beauty of a neatly arranged strawberry garden. care for strawberries directly, so that our tour not only feels satisfaction with the place, but also gains knowledge about caring for strawberries properly that we can apply someday. This study aims to determine the factors that influence tourist visits to strawberry plantations in the Tongkoh Tourism Area, Karo Regency. This research is a quantitative descriptive research. This study uses questionnaire data taken directly from visitors who are visiting the strawberry garden in the Tongkoh Tourism Area, Karo Regency. The sample in this study amounted to 94 samples, using accidental sampling technique (accidental Sample). The analytical method used is Multiple Linear Regression analysis. Based on the results of research on Factors Affecting Tourist Visits at Strawberry Gardens in Tongkoh Tourism Area, the authors can conclude that: (1) Strawberry price variables have no significant effect on tourist visits. (2) The variables of strawberry quality, service quality, and location have a significant effect on tourist visits.